Effect of Ethylene on the Uptake, Distribution, and Metabolism of Indoleacetic Acid-1-(14)C and -2-(14)C and Naphthaleneacetic Acid-1-(14)C - Beyer, Elmo M. (1970)
The effect of ethylene on the uptake, distribution, and metabolism of indoleacetic acid (IAA)-1-(14)C, IAA-2-(14)C, and naphthaleneacetic acid (NAA)-1-(14)C in cotton stem sections (Gossypium hirsutum L., var. Stoneville 213) was studied. Stem sections excised from plants pretreated with ethylene for 15 hours transported significantly less (14)C-IAA and (14)C-NAA than control sections. Concomitant features of the reduction of (14)C-IAA transport were an increase in decarboxylation and a trend toward a reduction in total uptake. With (14)C-NAA, however, total uptake was significantly increased, and decarboxylation was unaffected. (14)C-IAA was rapidly converted to indoleacetylaspartic acid and many other metabolites in both control and ethylene-pretreated stem sections. Following transport, similar amounts of (14)C-IAA were recovered in the apical absorbing portion of the control and ethylene-pretreated sections. Significantly more (14)C-IAA metabolites, however, were recovered in this region of the ethylene-pretreated sections. Conversely, (14)C-NAA was metabolized more slowly than (14)C-IAA under identical experimental conditions, with the only major metabolite being naphthaleneacetylaspartic acid. Following transport the apical absorbing portion of ethylene-pretreated stem sections contained significantly more (14)C-NAA than the controls. These results suggested that the disruption of auxin transport by ethylene cannot be explained in terms of a more rapid metabolism of auxin in the treated sections. The increased (14)C-IAA metabolites in the absorbing portion of ethylene-pretreated sections appear to be the result, rather than the cause, of the ethylene-mediated disruption of IAA transport.